Eisenhower and the mass media : peace, prosperity, & prime-time TV - Allen, Craig (Craig Mitchell) (The University of North Carolina Press, 1993)
Dwight D. Eisenhower presided over an unusual era of peace and prosperity during the 1950s, a period also known as television's "Golden Age." In this first comprehensive study of Eisenhower's mass communication practices, Craig Allen maintains that Ike's tremendous popularity was partly a result of his skillful use of the new medium of television to define and broadcast his achievements to the American public. Although John F. Kennedy has often been called the first TV president, Allen argues that Eisenhower rightfully deserves that title. Ike was an avid TV watcher, and he saw the medium as a breakthrough. He was aware of the changes television was creating in American society; thus he wasted little time in establishing TV as his dominant communication priority. Eisenhower presided over sweeping changes in the techniques and traditions of presidential communication. He was the first president to deliver televised "fireside chats," hold TV news conferences, conduct televised cabinet meetings, and hire a presidential TV consultant. Ike established the first White House TV studio and was the first president to actively engage in televised "photo opportunities." His 1956 reelection campaign defined much of what is known today as the "television campaign." Only one president since - Ronald Reagan - has left the White House with a higher approval rating from the American public, and Allen credits that achievement to Eisenhower's understanding and use of this new medium